Social media in an integrated marketing communication strategy - Lopez Y Gonzalez, Manuel (Kemi-Tornion ammattikorkeakoulu, 2012)
The objective of this research work is to find out how to integrate social media in Off-Road’s Finnmark marketing communications. One of the aims of this research is to help the case company to increase the usage of social media in their marketing strategy. The next objective is to develop a marketing strategy for Off-Road Finnmark, in order to assist the organization to implement social media. Relevant articles and literature was reviewed in order to have data to develop the literature review chapter. Using the data obtained from those sources it was possible to define the core concepts of this Thesis work, such as social media. Other aspects where included like the way small and medium size enterprises are currently employing social media, and the advantages and disadvantages of social media. This is was a qualitative research, and it used a triangulation method to recollect the data for the literature review. For the empirical part an in-depth interview was conducted with the administrative manager from ORF, Connie Graumann. This interview was done with the purpose to have a perspective of what was the organization’s understanding and implementation of social media. The interview was divided into two parts. The first part was done via email and the second part was held through a Skype call. Literature research and previous practical experience with the company helped to provide depth to the analysis of the current situation and implementation of social media within their IMC. The findings from my research demonstrated that although the company has started to integrate social media to their marketing communications there was still space for improvement. Due to some obstacles, Off-Road Finnmark has not been able to completely benefit from using social media. With the aid of the strategy that was developed in this research, the case company can continue finding ways to keep social media as a supporting tool within their integrated marketing communications. Keywords: social media, integrated marketing ...